Covid-19 and Higher Education Learning Ecosystem: Challenges and Way Forward - Garg, Suresh Chand; Sharma, Ramesh Chander (Indian Journal of Educational Technology, 2021)
In the history of humankind, interruption to education has been noticed earlier, however, the disruptions caused by COVID-19 pandemic are unprecedented. Affecting the whole world, it has halted our movement, which has been necessary to put a tab on the spread of virus. This also affected parents, teachers and students. World student and teacher population is facing challenging times in keeping pace with these happenings with the purpose of continuation of teaching learning during pandemic times. This paper discusses such challenges arising out of COVID-19 pandemic and proposes some way forward in dealing with this crisis.